Acricotopus indet. morphotype incurvatus: Description and genetics of a new Orthocladiinae (Diptera: Chironomidae) larval morphotype from the Tibetan Plateau - Laug, Andreas; Hamerlík, Ladislav; Anslan, Sten; Engels, Stefan; Turner, Falko; Wang, Junbo; Schwalb, Antje (Zootaxa, 2019)
High mountain ranges such as the Tibetan Plateau with an average altitude above 4500 m are topographically complex formations. Elevational gradients, physiographic diversity and climatic heterogeneity have led to highly biodiverse ecosystems in these regions. Mountain ranges can be seen as cradles of evolution and harbour, due to their unique characteristics, a high number of highly adapted species. At the same time these areas are hard to access and therefore taxonomic information is limited. Here we describe a new Acricotopus (Diptera: Chironomidae: Orthocladiinae) larval morphotype occurring in lakes and ponds of differing salinity and water depths located on the Southern and Central Tibetan Plateau. The description is based on larvae and their genetics (ribosomal 18S, 28S and mitochondrial COI sequences) collected from a shallow pond in close proximity to the large saline lake Selin Co. Larvae of Acricotopus indet. morphotype incurvatus are characterized by a mentum with a cluster of lateral teeth, partially folded inwards, a mandible with a toothed lobe in addition to four inner teeth and a sclerotized plate positioned behind the mentum. Up to now, these morphological features have only been found in early instars of other Acricotopus species. The proposed morphotype name is inspired by the peculiar form of the mentum.